Prevalence of cryptosporidium parvum with oxidative stress and antioxidant status in sucker cattle calves suffering from diarrhea. - Osman, Fathy Ahmad (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The study was carried on 160 newborn calves (140 calves suffering from diarrhea and 20 calves, clinical and laboratory healthy and used as a control group),classified according to age into three group; group A(2day-1month),group B (1month-2months) and group C(2months-3months),all calves selected from three different area according to the source of water, area 1(Deseret area),45 calves and used artesian water, area 2(Sewage area),50 calves and used sanitation water and area 3(Village area),45 calves and used Nile water. The study aimed to determine the prevalence of C. parvum, effect of water source on the prevalence of infection and summarize the cellular oxidant and antioxidant systems in newborn calves naturally infected. Fecal and blood samples were collected from all calves under the study for analysis ,the result revealed high percent of infection between calves(65%,44.44% and 20%) in area 2,3 and 1,respectively but in relation to age the result revealed that group A(26.66%,80.55% and 54.285) fallowed with group B(11.11%,16.66% and14.28%)in area 1,2 and 3 respectively, while group C revealed infection in area 2 only in ratio of 12.5%.Oxidative stress indicators revealed that highly significant increase in Malondialdehyed (2.99±0.11)with highly significant decrease in antioxidant parameters (Catalase and Superoxide dismutase enzymes),0.88±0.66 and 51.8±16.4,respectivelly.